2012
DOI: 10.3109/0886022x.2012.718710
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Protein-energy Wasting and Its Various Types in Iranian Hemodialysis Patients: A New Classification

Abstract: Background: This study was designed to determine the prevalence of protein-energy wasting (PEW) and its various types in hemodialysis (HD) patients in Tehran, Iran. Methods: For this cross-sectional study, 291 HD patients were randomly selected. The nutritional status of the patients was determined by subjective global assessment (SGA) and their dietary intakes were assessed using a 4-day dietary recall. In addition, serum high-sensitive C-reactive protein (hs-CRP) was measured. Results: The prevalence of mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Our study showed that the prevalence of dynapenic obesity and sarcopenic obesity were 11.4% and 3.8%, respectively, in adult PD patients in peritoneal dialysis centers in Tehran, Iran. The reason for this low prevalence of obesity, including dynapenic obesity and sarcopenic obesity, in Iranian PD patients is a high prevalence of protein-energy wasting in dialysis patients in Iran [26]. We found no study on the prevalence of dynapenic obesity in CKD patients, including PD patients, to compare with the results of our study.…”
Section: Discussionmentioning
confidence: 62%
“…Our study showed that the prevalence of dynapenic obesity and sarcopenic obesity were 11.4% and 3.8%, respectively, in adult PD patients in peritoneal dialysis centers in Tehran, Iran. The reason for this low prevalence of obesity, including dynapenic obesity and sarcopenic obesity, in Iranian PD patients is a high prevalence of protein-energy wasting in dialysis patients in Iran [26]. We found no study on the prevalence of dynapenic obesity in CKD patients, including PD patients, to compare with the results of our study.…”
Section: Discussionmentioning
confidence: 62%
“…This finding is in agreement with those of smaller studies in Iran. Tabibi et al, in a study from Tehran‐Iran, showed that 60.5% of HD patients had mild‐to‐moderate PEW and 1% had severe PEW 24 . In the study by Saran et al, the prevalence of mild‐to‐moderate and severe PEW was 24% and 8%, respectively 25 .…”
Section: Discussionmentioning
confidence: 97%
“…Protein‐energy malnutrition (PEM) is highly prevalent in individuals undergoing haemodialysis (HD) because of a reduced protein and energy intake, inflammation, resistance to anabolic hormones such as insulin and growth hormone, and the loss of amino acids and other nutrients in the dialysate and catabolism of muscle protein .…”
Section: Introductionmentioning
confidence: 99%